Ethiopia - Diversifying the Rural Economy : An Assessment of the Investment Climate for Small and Informal Enterprises - World Bank (World Bank, 2012)
Ethiopia's rural non-farm sector is significant and participation is increasing. The sector is particularly important for women and poorer households. Non-farm enterprises provide income-earning opportunities to those lacking alternative options and supplementary income for farming households. This report is organized into seven chapters. The first chapter lays the analytical groundwork for assessing the rural investment climate in Ethiopia and establishes a broader context for the empirical findings. The second chapter analyzes size and basic enterprise characteristics. The third chapter sheds light on the role of women in rural entrepreneurship. The fourth chapter analyzes enterprise dynamics: start-up, closure, and growth. The fifth chapter is dedicated to the welfare effects of rural enterprises, in particular their impact on food security and distributional effects. The sixth chapter compares rural and urban informal enterprise performance and considers the role of small market towns. The final chapter summarizes the findings and offers reflections for policy.